EVASÃO DOS ESTUDANTES DO CURSO DA ADMINISTRAÇÃO: UM ESTUDO DE CASO - da Silva, Daiane (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2021)
Introduction: Entering university is a lifelong dream for many people, but continuing at university is not as simple as it sounds. The present research sought to analyze which the main causes of dropout influenced the dropout from the Administration course. Objective: the research aimed to analyze the factors that contributed to the evasion of students from the Administration Course, considering the perception of evaders. Method: the present study is characterized in terms of objectives, as a descriptive research using a predominantly qualitative approach, the procedures used were questionnaires. The one applied with the students of the Administration course who were locked out, cancellation and withdrawal from 2014 to 2018 at the Western University of Santa Catarina - Unoesc de Maravilha. Being investigated population of 81 dropout students, getting 44 respondents. Results: questioned about the reasons related to dropping out of the university course in administration were: changing the curriculum, financial difficulties, distance, not adapting to the course, not reconciling schedules, family problems, moving to another city, not identifying with the course, illnesses, seeking knowledge because it was only involved in the field of work in which I was working at the time, the influence of parents, family and friends, benefits such as scholarships, these were the problems that influenced the withdrawal from the course. Conclusion: currently, institutions have been undergoing many changes, going from a cycle where the offer of courses and vacancies is greater than the demand, to a scenario of great competition. This study made it possible to observe that institutions, especially on-site ones, bring a differential, but also demand time, effort, study and financial conditions from academics. The research sought to analyze what the main causes of dropouts influenced the dropout from the Administration course, with the aim of bringing subsidies through research, indicating alternatives to reduce dropouts in the Graduate Program in Administration at the University of the West of Santa Catarina – Unoesc. It is concluded that the research and its results are an attempt to help transparency in the quality of the course management, also to collaborate with the permanence and decrease in academic dropout. Obtaining data that the research provided us in the objectives of identifying which problems were related to dropping out of the course, has a breadth of knowledge in different environments, related to issues of the management process of organizations having various segments for market performance, not only needing to be a businessman or owner of a company to undertake the graduation in the course observing different points of action, even adding specialized knowledge in the area that generates the most interest and attention to them.